SPATIAL MODELING IN TRADISONAL GOLD MINING HG (MERCURY) POLLUTION IN GORONTALO - Prasetya, Ekawaty; Makkulawu, Andi (Transpublika Publisher, 2024)
This study focuses on spatial modeling, ecological risk analysis, and human health risk analysis concerning mercury (Hg) pollution in traditional gold mining areas in Gorontalo. The research aims to safeguard both ecological balance and the health of gold mining workers exposed to mercury in wet and dry deposition, as well as dug well water, particularly in burning areas where amalgam gold mining occurs. The study comprises four main stages: sampling and coordinate determination, THg level examination in water and deposition samples, spatial analysis, and ecological and health risk assessments. Unlike previous studies, this research primarily focuses on mercury intake through inhalation of dry deposition and oral ingestion of dug well water from burning amalgam, excluding other exposure routes such as food and skin contact. A comprehensive literature review was conducted using electronic databases such as ScienceDirect, JOVE, Google Scholar, and SpringerLink. The search employed keywords like